En højskolevinter. Elevdagbog fra provisorieårene i 1880erne udgivet af Roar Skovmand - Grosen, Uffe (Grundtvig-studier, 1969)
A Winter at a Folk High-School.The Diary of a Pupil, from the “ Provisional Period” of the 1880’s. (Ed. By Roar Skovmand). Reviewed by Uffe Grosen.Hitherto, in the literature about the history of the folk high-school, there has been no diary to give us clear evidence about the folk high-school as experienced here and now by one of its pupils. The present diary provides us with source material of this very kind, the author being, moreover, an intelligent, mature, and independent mind, a young qualified carpenter, who took an active part as a leader in the gymnastic movement in Stevns, his native district, and joined the winter course of 1884-85 at Vallekilde Folk High-School. He was attracted first of all by Ernst Trier’s strong personality and by Andreas Bentsen, the leader of the artisan department. The diary reveals a listener who is both deeply moved and critical. He refuses to be swept along spiritually, and remains his own self, even when seas run high. The diary was kept in the home of the author Niels Nielsen until his death in 1919. After the death of his wife in 1946 it came into the possession of his daughter Ellen Karlshøj, who died in 1968. It has now, through the agency of the Institut for dansk Skolehistorie, been edited by Prof. Roar Skovmand, and no editor, it may be safely said, could possibly be better qualified for the task. The diary gives an authentic impression of the way in which the pupils were influenced by Ernst Trier. However overwhelming his personality may be said to have been, he appealed to the love of independence in the young pupils. In the preface the editor rightly refers to a letter from Ernst Trier expressing the wish that his views may not be “glued on to the pupils” but that they will be “roused to reflection, to form their own opinions freely and independently”.